Il futuro dell’unione europea dopo il trattato di lisbona: sussidiarietà’, eteronomia costituzionale e ricerca di un equilibrio neo-gotico (2009)
The scientific research on the future of the European Union does not allow a right explanation of this political and legal phenomenon. This is evidenced by economic investigations on the financial market without real social referents, or sociological investigations on differences in the social identity without taking into account the legal norms. Therefore, this work is developed from the perspective of legal sociology, to sustain the thesis that the political and legal project of the European Union, nowadays corresponds to a project of defensive modernization.